THEORETICAL AND PRACTICAL FOUNDATIONS FOR IMPROVING EQUITY ACCOUNTING IN JOINT-STOCK COMPANIES UNDER IFRS (International Congress on Economics, Management and Business Studies, 2026)
This article examines the theoretical, methodological, and practical foundations for improving equity accounting practices in joint-stock companies based on International Financial Reporting Standards (IFRS). The study focuses on the recognition, measurement, presentation, and disclosure of equity components, including share capital, additional paid-in capital, revaluation reserves, retained earnings, and other equity instruments. Particular attention is paid to the role of IFRS in enhancing financial transparency, strengthening corporate governance, improving investor confidence, and increasing the comparability of financial statements.
Keywords: joint-stock company, equity, International Financial Reporting Standards, IFRS, corporate governance, capital market, financial transparency, investment attractiveness.